2021
DOI: 10.1002/npr2.12223
|View full text |Cite
|
Sign up to set email alerts
|

Searching for biomarkers in schizophrenia and psychosis: Case‐control study using capillary electrophoresis and liquid chromatography time‐of‐flight mass spectrometry and systematic review for biofluid metabolites

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
(83 reference statements)
0
0
0
Order By: Relevance
“…A few of these scholars support the idea that lactate levels are reduced in schizophrenia, [58] whereas abnormally elevated lactate in schizophrenia is recognized by most researchers. [21,43,[55][56][57][59][60][61] Regenold WT et al first found that lactate concentrations in the cerebrospinal fluid of patients with schizophrenia and bipolar disorder were increased by 23% and 34%, respectively, compared to healthy control. [55] Higher levels of lactate were also present in the anterior cingulate cortex (ACC) of SCZ patients, which was associated with poorer cognitive and functional performance, and the abnormally high levels of lactate in this brain region are thought to be related to increased glycolysis due to mitochondrial dysfunction.…”
Section: Analysis Of Lactate Testing Results In Patients With Schizop...mentioning
confidence: 99%
See 3 more Smart Citations
“…A few of these scholars support the idea that lactate levels are reduced in schizophrenia, [58] whereas abnormally elevated lactate in schizophrenia is recognized by most researchers. [21,43,[55][56][57][59][60][61] Regenold WT et al first found that lactate concentrations in the cerebrospinal fluid of patients with schizophrenia and bipolar disorder were increased by 23% and 34%, respectively, compared to healthy control. [55] Higher levels of lactate were also present in the anterior cingulate cortex (ACC) of SCZ patients, which was associated with poorer cognitive and functional performance, and the abnormally high levels of lactate in this brain region are thought to be related to increased glycolysis due to mitochondrial dysfunction.…”
Section: Analysis Of Lactate Testing Results In Patients With Schizop...mentioning
confidence: 99%
“…In addition to the brain, blood lactate levels are commonly elevated in patients with schizophrenia. [21,[59][60][61] One study interpreted elevated lactate levels in venous blood of SCZ patients as gastric acid retention and tissue-derived hypoxia. [21] Interestingly, serum lactate levels seem to fluctuate at different stages of schizophrenia.…”
Section: Analysis Of Lactate Testing Results In Patients With Schizop...mentioning
confidence: 99%
See 2 more Smart Citations
“…and univariate approaches (e.g., t-tests with multiple testing corrections). Seven studies found >10 significant metabolites associated with antipsychotic use, while six studies found <10 metabolites, and one study found no associations [22] Fifty-four associations with metabolite classes were identified across all studies, with carboxylic acids being the most commonly identified in nine studies. General metabolite class identifications are detailed in Table 2, and in-depth findings are provided in Supplementary Table S2.…”
Section: Untargeted Metabolomic Studiesmentioning
confidence: 91%